Pathology of Oviduct in Sub Optimally Producing Commercial Layer Chicken - Srinivasan , P.; Balasubramaniam, G.A.; Gopalakrishnamurthy, T.R.; Balachandran, P. (International Journal of Poultry Science, 2012)
Pathology of oviduct in sub optimally producing commercial layer chicken were investigated in five flocks. Suboptimal production was commonly noticed between 23rd to 45th wk of age. The production drop ranged from 5 to 12 per cent below the expected egg production. The morbidity and mortality rates varied from 5 to 11 and 0.2 to 2 percent, respectively. The antibody HI titres for NDV (128-445.7) IB (45.3-128) and EDS -76 (2 to 4) were within the normal range. ELISA titre for MG and MS was below 269. The heterophil : lymphocyte (H:L) ratio was above the normal level in all the five flocks and it was more elevated in younger (0.97) compared to older (0.63) flocks. Bacteriological and virological examination revealed no organisms of any etiological significance. Grossly, regression, deformation and loss of hierarchy in ovarian follicles were noticed. The left oviduct was, short, narrow and thread like structure in few birds and in the remaining cases partial atrophy with demarcation were noticed. On opening, the mucosal surface of the affected oviduct lost its glistening appearance and the folds were markedly reduced in height and width. Histopathologically, deciliation of surface epithelium, degeneration and involution of the glandular tissues with well developed connective tissue matrix and mild to moderate mononuclear cells infiltration in all the parts of oviduct were noticed. Absence of etiological agents and elevation of H:L ratio suggest that the atrophy of oviduct in sub optimally producing flocks may be due to non specific stress experienced by the commercial layer chickens.